Newsrooms in Conflict. Journalism and the Democratization of Mexico - Sajna, Radoslaw (Departamento de Psicología y Comunicación de Texas A&M International University | Facultad de Trabajo Social y Desarrollo Humano de la Universidad Autónoma de Nuevo León, 2013)
Sallie Hughes (2006) Newsrooms in Conflict. Journalism and the Democratization of Mexico. University of Pittsburgh Press; Pittsburgh.